KRAS, YAP, and obesity in pancreatic cancer: A signaling network with multiple loops. (February 2019) - Eibl, Guido; Rozengurt, Enrique
Abstract: Pancreatic ductal adenocarcinoma (PDAC) continues to be a lethal disease with no efficacious treatment modalities. The incidence of PDAC is expected to increase, at least partially because of the obesity epidemic. Increased efforts to prevent or intercept this disease are clearly needed. Mutations in KRAS are initiating events in pancreatic carcinogenesis supported by genetically engineered mouse models of the disease. However, oncogenic KRAS is not entirely sufficient for the development of fully invasive PDAC. Additional genetic mutations and/or environmental, nutritional, and metabolic stressors, e.g. inflammation and obesity, are required for efficient PDAC formation with activation of KRAS downstream effectors. Multiple factors "upstream" of KRAS associated with obesity, including insulin resistance, inflammation, changes in gut microbiota and GI peptides, can enhance/modulate downstream signals. Multiple signaling networks and feedback loops "downstream" of KRAS have been described that respond to obesogenic diets. We propose that KRAS mutations potentiate a signaling network that is promoted by environmental factors. Specifically, we envisage that KRAS mutations increase the intensity and duration of the growth-promoting signaling network. As the transcriptional activator YAP plays a critical role in the network, we conclude that the rationale for targeting the network (at different points), e.g. with FDA approved drugs such as statins and metformin, is therefore compelling.